Distortional Influence of Pallet Rack Uprights Subject to Combined Compression and Bending. (November 2016) - Bonada, J.; Pastor, M.M.; Roure, F.; Casafont, M.
Abstract: A pallet rack is a structure in which the beams and uprights are cold-formed steel sections. The beam-upright connections are normally clipped in order to select the beam levels required and for ease of assembly. For this reason, the uprights contain holes and perforations distributed along their length. The complexity of these components, with local, distortional and torsional/flexural buckling behaviour, represents a challenge in structural design. The loads acting on the structure are induced by the weight of pallets to be stored, and transmitted to the uprights by the semi-rigid connection system. Therefore, the uprights are thin-walled singly symmetrical perforated open cross-sections bearing axial load and bending moment simultaneously. The main objective of this paper is to analyse the influence of the bending moment on the load bearing capacity of rack uprights subject to axial load together with bending moment. Bending is induced by means of axial forces eccentrically applied. The influence of bending on the strength capacity of rack uprights is analysed through finite element analysis, where residual stresses and strength enhancement induced during cold forming of sections are also considered. Experimental tests have been performed reproducing the load conditions in order to validate the FEA results. The ultimate load has also been calculated according to the European Standards and compared to experimental results.